Akureyri District Heating Project - Lund, John W. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1977)
Details of planning and projected implementation of the project that will provide space heating by 1981 for Akureyri, a city of 12,000 in northern Iceland, are given. Three wells have been drilled; a fourth is in progress. Economics of the project are discussed